Correlation between Mechanism of Carbapenem Resistance and in vitro Efficacy of Ceftazidime-Avibactam and Meropenem-Vaborbactam on Carbapenem-Resistant Enterobacterales and Pseudomonas Aeruginosa - Ali, Fatima; Mirza, Irfan Ali; Waseem, Hafsa; Khursheed, Umer; Zafar, Humaira; Sarwar, Maryiam (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the mechanism of Carbapenem resistance, type of Carbapenemase produced and in vitro efficacy of Ceftazidime-Avibactam (CAZ-AVI) and Meropenem-Vaborbactam (MEV) against Carbapenem-resistant Enterobacterales and in vitro efficacy of Ceftazidime-Avibactam against Carbapenem-resistant Pseudomonas aeruginosa. Study Design: Cross-sectional study. Place and Duration of Study: Microbiology Department, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Mar to Aug 2020. Methodology: The mechanism of Carbapenem resistance in Enterobacterales and P.aeruginosa was determined by mCIM and eCIM methods. In vitro, the susceptibility of isolates to Ceftazidime-Avibactam and Meropenem-Vaborbactam was determined by disk diffusion technique according to CLSI 2020 guidelines. Results: Out of 249 Carbapenem -resistant isolates, there were 192(77.1%) Enterobacterales and 57(22.9%) P.aeruginosa. From 192 Enterobacterales, 174(90.6%) were Carbapenemase producers while 18(9.4%) used ‘other mechanisms. From 174 Carbapenemase producers, metallo-β-lactamases were produced by 141(73.4%) while serine Carbapenemases by 33(17.2%). Out of 33 serine Carbapenemase producers,19(57.6%) were sensitive to CAZ-AVI and 6(18.2%) to MEV. Out of 141 MBL producers, 31(22%) were sensitive to CAZ-AVI and 18(12.8%) to MEV. Out of 57 P.aeruginosa, 30(52.6%) were Carbapenemase producers and 1(3.4%) were sensitive to CAZ-AVI while 27(47.4%) were non-Carbapenemase producers and 13(48%) were sensitive to CAZ-AVI. MBL production predominated. Conclusion: The in vitro efficacy of these antibiotics against MBL producers and serine Carbapenemase producers was not satisfactory.